LINES OF ESCAPE: SOCIAL CLASS AS A FACTOR IN LESBIAN RESISTANCE (Interdisciplinary Studies Journal, 2025)
This article addresses the preservation of lesbian memory through the intersection of social class and resistance to historical erasure. By analyzing historical figures such as Anne Lister and Lota de Macedo Soares, the text demonstrates how class privilege allowed some lesbian women to keep their existences recorded, while lesbians from lower classes had their memories systematically erased. One of the main concepts addressed to justify this erasure is the idea of compulsory heterosexuality, which views heterosexuality as an instrument of control over female sexuality with various implications on women’s lives, and which has also impacted the preservation of lesbian memory over time.
Keywords: Memory; Political Resistance; Visibility; Class